2018
DOI: 10.21475/ajcs.18.12.10.p1197
|View full text |Cite
|
Sign up to set email alerts
|

Alleviation of chilling injury induced by cold quarantine treatment in Midknight Valencia and Lane Late sweet orange fruit

Abstract: Cold quarantine treatment (1°C for 21 days) induces chilling injury (CI) in sweet orange fruit. We investigated the effects of different treatments such as hot water dip (HWD, 50 °C) alone or combined with thiabendazole (TBZ) five-minute, different concentrations of salicylic acid (SA), methyl jasmonate (MJ) one-minute dip and fumigation of nitric oxide (NO) two-hour and ethylene (ET) (six-hour) on CI and fruit quality following 21 days cold quarantine treatment and 10-day at ambient temperature in 'Lane Late'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…PAL activity has been considered as a defence mechanism of cold stored fruit in response to chilling stress [8,28,33]. Cold temperature can enhance PAL activity in blood orange by upregulating PAL codifying genes in response to chilling stress [9]. In this sense, PAL mRNA accumulated in mandarin fruit during storage at low temperature (2 • C), which was related to the sensitivity of citrus fruit to CI [34].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PAL activity has been considered as a defence mechanism of cold stored fruit in response to chilling stress [8,28,33]. Cold temperature can enhance PAL activity in blood orange by upregulating PAL codifying genes in response to chilling stress [9]. In this sense, PAL mRNA accumulated in mandarin fruit during storage at low temperature (2 • C), which was related to the sensitivity of citrus fruit to CI [34].…”
Section: Discussionmentioning
confidence: 99%
“…The common responses include changes in cell structure, fatty acid saturation index, lipid peroxidation, electrolyte leakage (EL), proline content, hydrogen peroxide (H 2 O 2 ), malondialdehyde (MDA), activity of antioxidant enzymes and epidermis structure, among others [8]. In addition, chilling stress can change the cellular metabolism and reduce cell energy status, leading to chilling injury (CI) symptoms such as scalding, rind pitting and necrotic areas, watery breakdown and browning [8,9]. Postharvest treatment by hot water dipping (HWD, 3 min at 50 • C) and hot air treatment (HAT, 37 • C for 48 h) on blood orange fruit during cold quarantine at 1 • C for 16 days, showed that HWD and HAT similarly reduced CI in all cultivars, and neither treatment caused visible damage to the fruit [10].…”
Section: Introductionmentioning
confidence: 99%
“…The common responses include changes in cell structure, fatty acid saturation index, lipid peroxidation, electrolyte leakage (EL), proline content, hydrogen peroxide (H2O2), malondialdehyde (MDA), activity of antioxidant enzymes and epidermis structure, among others. In addition, chilling stress can change the cellular metabolism and reduce cell energy status and leading to chilling injury (CI) symptoms such scalding, rind pitting and necrotic areas, watery breakdown, and browning [8][9][10].…”
Section: Introductionmentioning
confidence: 99%